Two-year single-center experience with the 'Baby Trevo' stent retriever for mechanical thrombectomy in acute ischemic stroke. (9th June 2016) - Kühn, Anna Luisa; Wakhloo, Ajay K; Lozano, J Diego; Massari, Francesco; De Macedo Rodrigues, Katyucia; Marosfoi, Miklos G; Perras, Mary; Brooks, Christopher; Howk, Mary; Rex, David E; Gounis, Matthew J; Puri, Ajit S
Abstract : Objective: To evaluate the safety and efficacy of the 'Baby Trevo' (Trevo XP ProVue 3×20 mm Retriever) stent retriever for large vessel occlusions (LVOs) in acute ischemic stroke (AIS). Materials and methods: We retrospectively analyzed our stroke database and included all patients treated with the Baby Trevo for distal LVOs in AIS. Patient gender, mean age, vascular risk factors, National Institutes of Health Stroke Scale (NIHSS) score at presentation, and modified Rankin Scale (mRS) score at baseline and 90-day follow-up were documented. Reperfusion rates for the vessels treated were recorded using the Thrombolysis in Cerebral Infarction (TICI) classification. Occurrence of vasospasm and new or evolving infarcts in the treated vascular territory was documented. Results: Thirty-five subjects with a mean NIHSS score of 18 were included. The Baby Trevo device was used in 38 branches of the anterior and posterior circulations. TICI 2b/3 blood flow was restored after one single pass in 20/38 (52.6%) and after two or three passes in 11 vessels. The remaining vessels required either more than three passes, showed less than a TICI 2b/3 reperfusion (n=3), or demonstrated failure to retrieve the clot (n=4). TICI 2b/3 reperfusion was achieved in 30 patients (85.7%). No vessel injuries, rupture, or significant vasospasm were seen. Overall, a mRS score of ≤2 was seen in 56.5% of the subjects successfully treated with the Baby Trevo at 90 days and in 81.3% of surviving patients; seven patients died (20%). Conclusions: Our preliminary data suggest that the 'Baby Trevo' achieves a high recanalization rate without any significant risk. Larger cohort studies are needed to validate the clinical benefit.